UPAYA PENERAPAN PEMBELAJARAN AL-QUR’AN METODE TILAWATI DI MINU MAUDLU’UL ULUM PURWANTORO KECAMATAN BLIMBING KOTA MALANG - Nuril Khausumah; Khoirul Asfiyak; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This method uses tilawati learning method in MINU maudlu'ul ulum purwantoro blimbing sub-district of Malang. In the implementation of learning the Qur'an, tilawati method, children who have not read, the Qur'an, can read well, and also makes it easier for teachers to complete materials that use Arabic writing, such as Arabic language lessons, the Qur'an 'a hadith in reading short letters. This research was conducted at the Madrasah MINU maudlu'ul ulum purwantoro Blimbing sub-district of Malang. the purpose of this study was to describe the learning of the method of al-Qur'an tilawati in MINU maudlu'ul ulum purwantoro blimbing sub-district of Malang. using qualitative research with descriptive type. Data collection uses observation, interviews, and documentation. Data analysis using condensation data, display data and drawing and concluding conclusions. The results of this study are the ability to read the Qur'an students good in learning the Qur'an recitation method, and the strategies used in learning the Qur'an recitation method are classical individuals and reading reading techniques, and supporting factors that indicate facilities which supports, professional teachers, and the interests of student talent as for the inhibiting factors are attitude tolerance and time allocation.